2012
DOI: 10.1016/j.juro.2012.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The International Prostate Symptom Score Overestimates Nocturia Assessed by Frequency-Volume Charts

Abstract: The International Prostate Symptom Score nocturia score overestimated nocturia in most patients, as derived from a 7-day frequency-volume chart. When scoring International Prostate Symptom Score nocturia question 7, patients included a degree of bother. The correlation of question 7 with mean nocturia increased with frequency-volume chart duration until day 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Similar findings were concluded from a study by Yap et al that analyzed the relationship between IPSS and FVC in men with LUTS, regarding a better agreement at nocturia episodes and a trend toward overestimating symptoms when filling the IPSS . Also, Van Haarst et al found an overestimation of the IPSS nocturia score in 50% of patients as compared to the FVC …”
Section: Discussionsupporting
confidence: 84%
“…Similar findings were concluded from a study by Yap et al that analyzed the relationship between IPSS and FVC in men with LUTS, regarding a better agreement at nocturia episodes and a trend toward overestimating symptoms when filling the IPSS . Also, Van Haarst et al found an overestimation of the IPSS nocturia score in 50% of patients as compared to the FVC …”
Section: Discussionsupporting
confidence: 84%
“…This is due to the fact that these studies utilized the nocturia score of the IPSS when estimating nocturia episodes. Despite reports that the IPSS nocturia component was sufficient to represent the patient's nocturnal voiding habits, recent studies have highlighted the dissociation between what patient recalls when reporting IPSS and what actually occurs on FVC . By evaluating FVC for the possible etiology of nocturia, the present study was able to distinguish between nocturia associated with global polyuria, decreased nocturnal bladder capacity, frequency and nocturnal polyuria.…”
Section: Discussionmentioning
confidence: 68%
“…FVCs are beneficial when assessing patients with bothersome storage LUTS, particularly nocturia, as they can underpin categorisation of the underlying mechanism(s) [19][20][21]. FVCs are typically more accurate than patient recall [22,23], particularly for nocturia. However, FVC use may lead to a bladder training effect, and nights during FVC recording may be atypical since substantial variations in the frequency of nocturnal voids have been observed [24].…”
Section: Frequency-volume Charts and Bladder Diariesmentioning
confidence: 99%